Two-storeyed entrance gateway to the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Pictured here is a view of the two-storeyed entrance gateway to the Mahanaleshwar temple complex. The gateway is part of an enclosure wall that demarcates the boundaries of the complex on all four sides. Inside the enclosure walls are several temples, of which the shikhara (superstructure) of the Mahanaleshwar Temple is visible from the outside.